Investigation of N‐ and C‐Phosphanylation of [1, 2, 4]Triazolo[4, 3‐a]pyridines. Issue 4 (4th February 2015) - Marchenko, Anatoliy P.; Koidan, Heorgiy N.; Kirilchuk, Andrey A.; Rozhenko, Alexander B.; Yurchenko, Aleksandr A.; Kostyuk, Aleksandr N.
ABSTRACT Synthesis and deprotonation of N‐phosphanylated[1, 2, 4]triazolo[4, 3‐a]pyridinium triflates were investigated. Phosphanylation by t‐Bu2PCl proceeds at N1 of starting triazolo‐pyridines. According to density functional theory calculations, deprotonation of the formed salt gives abnormal carbenes, which decompose by opening of the triazole cycle. Treatment by chlorodiphenylphosphane leads to an equilibrium mixture of N1‐ and N2‐phosphanylated salts, which under addition of base yields normal carbene that rapidly rearranges to form C‐phosphanylated product. Mechanisms of the reactions are discussed.